Gambaran Penggunaan Obat Analgetik Secara Rasional Dalam Swamedikasi Pada Masyarakat PKS Balam, Desa Balai Jaya KM. 31 Kecamatan Balam Sempurna, Kabupaten Rokan Hilir, Riau - Lia Rahel Beniger Sipahutar; Henny Erina Saurmauli Ompusunggu; Runggu Retno J. Napitupulu (Nommensen Journal of Medicine, 2021)
Background: Analgesics are a type of medicine used to ease the sore. Certain types of analgesic drugs can be purchased by common people independently. This thing can be problematic if the analgesic drugs are not being used accordingly, the occurrence of unwanted side effects, for instance. The objective of this study is to find out an overview of analgesic drugs in self-medication towards the people of PKS Balam. Method: This study is a descriptive research. The respondents of this research are as many as 118 people of PKS Balam, which are chosen by using purpose sampling technique. An overview on the use of analgesic drugs in self-authentication in self-medication is acquired from questionnaire result. Result: Majority of respondents who consume analgesic drugs by self-medicating more than once a month complain to experience most frequent headache. Most common analgesic drug consumed is paracetamol. Majority of respondents initially read the brochure of medicine they are about to consume, but most of them understand only some information provided in the brochure. Majority of respondents acquired analgesic drugs purchased from drugstore. The most experienced side effects after consuming analgesic drug is sleepiness. Due to limited level of knowledge, majority of respondents will stop consuming the medicines and go to see the doctor when they experience side effects. Conclusion: The people of PKS Balam generally consume analgesic drugs by self-medicating more than once a month by initially reading the information about analgesic medicine they are about to consume.